Gerakan Bersama Masyarakat Untuk Meningkatkan Derajat Kesehatan Lansia Hipertensi Melalui Penerapan Terapi Menanam di Badung Bali - Martini, Ni Made Dwi Ayu; Sari, Ni Luh Putu Dian Yunita; Darmaja, Ketut (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2026)
Hypertension is one of the degenerative diseases that is a priority for treatment in the elderly. In addition to optimizing the coverage of health services, improving the ability of the elderly to care for themselves at home is an equally important focus. Regular physical activity is one of the management strategies recommended by the Indonesian government. One modality that can be applied is gardening therapy, which is known to help control blood pressure and reduce anxiety. Nurses play a role in enhancing self-efficacy and the ability of the elderly to manage their blood pressure. This program aims to introduce and implement gardening therapy for the elderly with hypertension. The method used is divided into three sessions: education, sharing, and practice. The activities were carried out in May 2024. The participants included 84 elderly individuals, 5 community health workers, and 4 healthcare center staff. The evaluation of the program results showed an increase in the knowledge and skills of the target group. It is hoped that elderly individuals with hypertension can continuously implement gardening therapy at home to improve their health status